Molecular marker testing and reporting completeness for adult-type diffuse gliomas in the United States. Issue 1 (7th October 2022) - Neff, Corey; Cioffi, Gino; Waite, Kristin; Kruchko, Carol; Barnholtz-Sloan, Jill S; Ostrom, Quinn T; Iorgulescu, J Bryan
Abstract: Background: A newly developed brain molecular marker (BMM) data item was implemented by US cancer registries for individuals diagnosed with brain tumors in 2018—including IDH and 1p/19q-co-deletion statuses for adult-type diffuse gliomas. We thus investigated the testing/reporting completeness of BMM in the United States. Methods: Cases of histopathologically confirmed glioblastoma, astrocytoma, and oligodendroglioma diagnosed in 2018 were identified in the National Cancer Database. Adjusted odds ratios (ORadj ) and 95% confidence intervals (CI) of BMM testing/reporting were evaluated for association with the selected patient, treatment, and facility-level characteristics using multivariable logistic regression. As a secondary analysis, predictors of MGMT promoter methylation testing/reporting among IDH-wildtype glioblastoma individuals were assessed. Key limitations of the BMM data item were that it did not include any details regarding testing technique or assay type and could not distinguish between a lack of testing and a lack of cancer registry reporting of testing results. Results: Among 8306 histopathologically diagnosed adult-type diffuse gliomas nationally, overall BMM testing/reporting completeness was 81.1%. Compared to biopsy-only cases, odds of testing/reporting increased for subtotal (ORadj = 1.38 [95% CI: 1.20–1.59], P < .001) and gross total resection (ORadj =1.50 [95% CI: 1.31–1.72], P < .001). Furthermore, the odds were lowest at community centers (hospitals (67.3%; ORadj =0.35 [95% CI: 0.26–0.46], P < .001) and highest at academic/NCI-designated comprehensive cancer centers (85.4%; referent). By geographical location, BMM testing/reporting completeness ranged from a high of 86.8% at New England (referent) to a low of 76.0 % in the West South Central region (ORadj =0.57 [95% CI: 0.42–0.78]; P < .001). Extent of resection, Commission-on-Cancer facility type, and facility location were additionally significant predictors of MGMT testing/reporting among IDH-wildtype glioblastoma cases. Conclusions: Initial BMM testing/reporting completeness for individuals with adult-type diffuse gliomas in the United States was promising, although patterns varied by hospital attributes and extent of resection.